Kwame "Almighty" Akoto, The Supernatural Eyes of God - Meyer, Birgit (Conversations, 2014)
During a trip to Ghana in May 2010, I visited the roadside shop and atelier of painter Kwame Akoto, alias “Almighty,” a name he adopted so as to praise the power of God.